Adhesive composition, transparent sheet for solar cell module, and thin-film solar cell module
Patent Information
- Application Number
- JP2024232732
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-26
AI Technical Summary
【0015】 本開示においては、耐候性および透明性に優れる接着層を得ることが可能な接着剤組成物、ならびに、耐候性および透明性に優れる太陽電池モジュール用透明シートを提供することができるという効果を奏する。
Smart Images

Figure 2025041964000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive composition for use in solar cell modules, as well as a transparent sheet for solar cell modules and a thin-film solar cell module each using the same. [Background technology]
[0002] In recent years, solar cells have been attracting attention as a clean energy source due to the growing awareness of environmental issues. In general, a solar cell module has a structure in which a transparent substrate, a sealing material layer, a solar cell element, a sealing material layer, and a back protective sheet are laminated in this order from the light-receiving surface side. Conventionally, a glass substrate has been mainly used as the transparent substrate arranged on the outermost surface of the light-receiving surface side of a solar cell module.
[0003] Recently, as a response to the increasing demand for lighter solar cell modules and flexible solar cell modules, there has been an increasing demand for solar cell modules that use a resin sheet, instead of a glass substrate, as the transparent substrate placed on the outermost surface on the light-receiving side of the solar cell module.
[0004] Since solar cell modules are expected to be used outdoors for a long period of time, each component constituting the solar cell module is naturally required to have a high degree of durability so as to be able to withstand the harsh outdoor environment for a long period of time. In particular, when a resin sheet is used as a surface protective sheet, the surface protective sheet must have transparency unlike the back protective sheet disposed on the non-light-receiving side of the solar cell module, and must have weather resistance and barrier properties comparable to those of a glass substrate.
[0005] In order to meet these demands, a resin sheet has been proposed that is made of a multilayer sheet in which a barrier layer made of a vapor-deposited film or the like that imparts barrier properties and a fluorine-based resin layer that imparts weather resistance are laminated onto a base layer made of a resin base material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-140273 A Summary of the Invention [Problem to be solved by the invention]
[0007] In a resin sheet consisting of a multilayer sheet, each layer such as a base layer, a barrier layer, and a fluororesin layer are generally bonded by an adhesive layer. The surface protection sheet is a member placed on the outermost surface of the light-receiving surface side of a solar cell module, and is therefore placed in an environment with a particularly large amount of water vapor. In addition, the surface protection sheet becomes hot when the solar cell module is irradiated with sunlight. Therefore, when a multi-layer resin sheet is used as the surface protection sheet, if it is left in the high temperature and high humidity environment for a long time, the adhesive layer may deteriorate and cause delamination. The delamination of the surface protection sheet causes water vapor and oxygen to enter the inside of the solar cell module, which is one of the factors that deteriorate the performance of the solar cell module.
[0008] As an adhesive used in the adhesive layer, for example, a two-liquid adhesive composition having a base agent and a curing agent is known (see, for example, Patent Document 1). In addition, in a resin sheet consisting of a multilayer sheet, in order to protect the base layer and the barrier layer from ultraviolet light, it has been proposed to incorporate an ultraviolet absorber into the adhesive layer that is located closest to the light-receiving surface of the adhesive layers that constitute the resin sheet (see, for example, Patent Document 1).
[0009] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an adhesive composition for use in solar cell modules, which is capable of obtaining an adhesive layer having excellent weather resistance and transparency, and a transparent sheet for solar cell modules having excellent weather resistance and transparency. [Means for solving the problem]
[0010] The inventors of the present disclosure have conducted intensive research to solve the above problems, and have found that by using a polyol component having a polycarbonate skeleton, which is excellent in hydrolysis resistance, heat resistance, weather resistance, etc., as the polyol component of the main component of the adhesive composition, and adding 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine (hereinafter sometimes referred to as ultraviolet absorber A), which has high ultraviolet absorption ability and excellent weather resistance among ultraviolet absorbers, it is possible to improve weather resistance, particularly wet heat resistance and light resistance. However, it has been found that ultraviolet absorber A has low compatibility with polyol components having a polycarbonate skeleton, and when the content is increased to obtain the desired weather resistance, the transparency of the resulting adhesive layer is reduced. The inventors of the present disclosure have further studied and have found that by adding a mixture of 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (hereinafter sometimes referred to as ultraviolet absorber B), which have good compatibility with polyol components having a polycarbonate skeleton, in addition to ultraviolet absorber A, the ultraviolet absorber B surprisingly functions as a compatibilizer between the polyol component having a polycarbonate skeleton and ultraviolet absorber A, and compatibility is improved. The present disclosure is based on such findings.
[0011] One embodiment of the present disclosure is an adhesive composition for use in a solar cell module, the adhesive composition having a first agent and a second agent, the first agent comprising a polycarbonate-based polyol, a first ultraviolet absorber which is a mixture of 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, The adhesive composition includes a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine and a light stabilizer, the second agent includes a polyisocyanate compound, the content of the first ultraviolet absorber is 1 part by mass or more and 4 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol, and the content of the second ultraviolet absorber is 8 parts by mass or more and 10.5 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol.
[0012] Another embodiment of the present disclosure is a transparent sheet for a solar cell module having a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, wherein the weather-resistant adhesive layer is a polycarbonate-based polyurethane resin which is a reaction product of a polycarbonate-based polyol and a polyisocyanate compound, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. and a light stabilizer, wherein the content of the first ultraviolet absorber is 1 part by mass or more and 4 parts by mass or less relative to 100 parts by mass of the polycarbonate-based polyol, and the content of the second ultraviolet absorber is 8 parts by mass or more and 10.5 parts by mass or less relative to 100 parts by mass of the polycarbonate-based polyol.
[0013] Another embodiment of the present disclosure is a transparent sheet for a solar cell module having a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, wherein the weather-resistant adhesive layer is a polycarbonate-based polyurethane resin, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. a first ultraviolet absorber which is a mixture of 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)]-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer; and the transparent sheet for a solar cell module has a haze of 15% or less, a wavelength of 300 nm or more and 400 nm or less, and an illuminance of 1000 W / m 2 The present invention provides a transparent sheet for a solar cell module, which, when irradiated with light of 1000 nm or more, takes 500 hours or more until the reduction in total light transmittance of the transparent sheet for a solar cell module reaches 5%.
[0014] Another embodiment of the present disclosure provides a thin-film solar cell module having, in this order, a transparent substrate, a thin-film solar cell element, an encapsulant layer, and a back surface protective sheet, wherein the transparent substrate is the above-mentioned transparent sheet for a solar cell module, and the transparent sheet for a solar cell module is arranged such that the surface on the base layer side faces the thin-film solar cell element. Effect of the Invention
[0015] The present disclosure has the effect of providing an adhesive composition that can obtain an adhesive layer that has excellent weather resistance and transparency, and a transparent sheet for a solar cell module that has excellent weather resistance and transparency. [Brief description of the drawings]
[0016] [Figure 1]1 is a schematic cross-sectional view illustrating a transparent sheet for a solar cell module according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view illustrating a transparent sheet for a solar cell module according to the present disclosure. [Diagram 3] 1 is a schematic cross-sectional view illustrating a solar cell module according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms, and should not be interpreted as being limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those described above with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.
[0018] In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" is intended to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified. Also, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface" is intended to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified.
[0019] In this specification, the term "sheet" also includes a member called a "film." The term "film" also includes a member called a "sheet."
[0020] The adhesive composition, the transparent sheet for a solar cell module, and the thin-film solar cell module according to the present disclosure will be described in detail below.
[0021] A. Adhesive Composition The adhesive composition according to the present disclosure is used in a solar cell module, and has a first agent and a second agent, the first agent being a mixture of a polycarbonate-based polyol and 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. and a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine; and a light stabilizer, the second agent containing a polyisocyanate compound, the content of the first ultraviolet absorber being 1 part by mass or more and 4 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol, and the content of the second ultraviolet absorber being 8 parts by mass or more and 10.5 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol.
[0022] In the adhesive composition of the present disclosure, the first agent contains a polycarbonate-based polyol, and the polycarbonate-based polyol has a polycarbonate skeleton, and therefore has excellent hydrolysis resistance, heat resistance, and weather resistance, and therefore weather resistance, particularly wet heat resistance, can be improved. In addition, in the adhesive composition of the present disclosure, the first agent contains a specific second ultraviolet absorber, and the second ultraviolet absorber has high ultraviolet absorption ability and excellent weather resistance, and therefore weather resistance, particularly light resistance, can be improved. Furthermore, in the adhesive composition of the present disclosure, by using a specific first ultraviolet absorber and a second ultraviolet absorber in combination, the first ultraviolet absorber functions as a compatibilizer between the polycarbonate-based polyol and the second ultraviolet absorber, and compatibility can be improved, so that transparency can be improved. In addition, in the adhesive composition of the present disclosure, by using the first ultraviolet absorber and the second ultraviolet absorber in combination with a light stabilizer, weather resistance can be further improved. Therefore, by using the adhesive composition of the present disclosure, it is possible to obtain an adhesive layer that is excellent in weather resistance, particularly in moist heat resistance and light resistance, and also in transparency.
[0023] Each component of the adhesive composition of the present disclosure will now be described.
[0024] 1. First agent The first agent constituting the adhesive composition in the present disclosure contains a polycarbonate-based polyol, a first ultraviolet absorber which is a mixture of 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer. In addition, the content of the first ultraviolet absorber and the content of the second ultraviolet absorber are within a predetermined range.
[0025] (1) Polycarbonate-based polyol The polycarbonate-based polyol in the present disclosure is a polyol component that reacts with the polyisocyanate compound contained in the second agent to form a urethane bond.
[0026] The polycarbonate-based polyol is not particularly limited as long as it has a carbonate bond in the main chain and a hydroxyl group at the molecular end, and examples thereof include polycarbonate polyol and polycarbonate polyurethane polyol. Among them, the polycarbonate-based polyol preferably contains a mixture of polycarbonate polyol and polycarbonate polyurethane polyol. This can improve the adhesion and weather resistance of the adhesive layer formed using the adhesive composition. This is presumably because the urethane bond imparts flexibility and conformability to the adhesive layer, and the internal cohesive force is increased. In addition, the carbonate bond provides excellent weather resistance and resistance to moist heat.
[0027] (a) Polycarbonate polyol Polycarbonate polyol has carbonate bonds in the main chain and hydroxyl groups at the molecular terminals.
[0028] In the polycarbonate polyol, the number of hydroxyl groups in one molecule is 2 or more, may be 2 to 4, or may be 2 to 3, but is preferably 2. That is, examples of polycarbonate polyols include polycarbonate diols, polycarbonate triols, and polycarbonate tetraols, and polycarbonate diols are preferably used. In the case of polycarbonate diols, the viscosity is easily adjusted and the coating properties are good.
[0029] In addition, examples of polycarbonate polyols include aliphatic polycarbonate polyols and aromatic polycarbonate polyols. In addition, aliphatic polycarbonate polyols also include alicyclic polycarbonate polyols. Among them, aliphatic polycarbonate polyols are preferred. In an adhesive layer formed using the adhesive composition, flexibility can be imparted and brittleness can be suppressed.
[0030] In particular, the polycarbonate polyol is preferably an aliphatic polycarbonate diol.
[0031] The polycarbonate polyol can be obtained, for example, by the reaction of a carbonate compound with a polyol compound. Specifically, the aliphatic polycarbonate polyol can be obtained by the reaction of a carbonate compound with an aliphatic polyol. In addition, the aromatic polycarbonate polyol can be obtained by the reaction of a carbonate compound with an aromatic polyol.
[0032] Examples of the carbonate compound include alkylene carbonate, dialkyl carbonate, diaryl carbonate, etc. Examples of the alkylene carbonate include alkylene carbonate having an alkylene group having 2 to 6 carbon atoms, specifically ethylene carbonate, trimethylene carbonate, 1,2-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, 1,2-pentylene carbonate, etc. Examples of the dialkyl carbonate include dialkyl carbonate having an alkyl group having 1 to 6 carbon atoms, specifically dimethyl carbonate, diethyl carbonate, dipropyl carbonate, etc. Examples of the diaryl carbonate include diphenyl carbonate, etc. The carbonate compound may be used alone or in combination of two or more.
[0033] Examples of polyol compounds include diol compounds, triol compounds, and tetraol compounds, and preferably diol compounds are used. In the case of diol compounds, the viscosity is easily adjusted and the coating properties are good. Examples of polyol compounds include aliphatic polyols and aromatic polyols. Among them, since polycarbonate polyols are preferably aliphatic polycarbonate polyols, aliphatic polyols are preferred, and aliphatic diols are more preferred. Examples of the aliphatic diol include aliphatic acyclic diols such as monoethylene glycol, diethylene glycol, triethylene glycol, monopropylene glycol, dipropylene glycol, tripropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4 butanediol, 1,5-pentanediol, 1,6 hexanediol, 1,7-heptanediol, 1,9 nonanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, octanediol, 2-ethyl-1,6-hexanediol, and 2-methyl-1,8 octanediol; and alicyclic diols such as 1,3-cyclohexanediol and 1,4-cyclohexanediol. The polyol compounds may be used alone or in combination of two or more. When one kind of diol compound is used alone, a homopolycarbonate diol can be obtained, and when two or more kinds of diol compounds are used, a copolymer polycarbonate diol can be obtained.
[0034] The number average molecular weight of the aliphatic polycarbonate polyol is preferably, for example, 1000 or more and 2000 or less. By having the number average molecular weight within the above range, it is possible to easily react with the polyisocyanate compound contained in the second agent, and to improve the solubility in the solvent. In the production of aliphatic polycarbonate polyol, since the reactivity of the monomer is high and it is easy to increase the molecular weight, it is preferable to control the reaction rate, etc., in order to obtain a polycarbonate diol having a predetermined number average molecular weight.
[0035] In this specification, the number average molecular weight is a value measured by gel permeation chromatography (GPC) at room temperature using tetrahydrofuran as an eluent and a calibration curve obtained using standard polystyrene samples with known molecular weights.
[0036] (b) Polycarbonate polyurethane polyol Polycarbonate polyurethane polyol has carbonate bonds and urethane bonds in the main chain and hydroxyl groups at the molecular terminals.
[0037] In the polycarbonate polyurethane polyol, the number of hydroxyl groups in one molecule is 2 or more, may be 2 to 4, or may be 2 to 3, but is preferably 2. That is, examples of polycarbonate polyurethane include polycarbonate polyurethane diol, polycarbonate polyurethane triol, polycarbonate polyurethane tetraol, etc., and preferably polycarbonate polyurethane diol is used. In the case of polycarbonate polyurethane diol, the viscosity is easily adjusted and the coating property is good.
[0038] Polycarbonate polyurethane polyol can be obtained, for example, by reacting polycarbonate polyol with polyisocyanate.
[0039] The polycarbonate polyol used in the production of the polycarbonate polyurethane polyol can be the same as the polycarbonate polyol described in the above section "(a) Polycarbonate polyol."
[0040] The polyisocyanate is not particularly limited as long as it is a compound having two or more isocyanate groups in one molecule, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, etc. Among them, alicyclic polyisocyanates are preferred, and isophorone diisocyanate is more preferred.
[0041] The polycarbonate polyurethane polyol is preferably the reaction product of an aliphatic polycarbonate diol, 1,6-hexanediol, and isophorone diisocyanate.
[0042] The aliphatic polycarbonate diol used in the production of polycarbonate polyurethane polyol is a polyol and can react with isophorone diisocyanate to form a urethane bond. The aliphatic polycarbonate diol can be the same as the aliphatic polycarbonate diol described in the above section "(a) Polycarbonate polyol".
[0043] 1,6-hexanediol used in the production of polycarbonate polyurethane polyol is a polyol similar to aliphatic polycarbonate diol, and can react with isophorone diisocyanate to form a urethane bond. 1,6-hexanediol is a liquid at room temperature and can be dissolved in a solvent.
[0044] The isophorone diisocyanate used in the production of polycarbonate polyurethane polyol is an alicyclic polyisocyanate. Isophorone diisocyanate can react with the hydroxyl groups of aliphatic polycarbonate diol and 1,6-hexanediol to form a urethane bond.
[0045] A polycarbonate polyurethane diol solution can be obtained by dissolving an aliphatic polycarbonate diol, 1,6-hexanediol, and isophorone diisocyanate in a solvent, mixing, and reacting them by heating under reflux. In the above reaction, the hydroxyl groups at both ends of the aliphatic polycarbonate diol and 1,6-hexanediol react with the isocyanate groups of the isophorone diisocyanate to form a urethane bond.
[0046] In the production of polycarbonate polyurethane diol, the blending amount of 1,6-hexanediol is, for example, preferably 5 parts by mass or more and 15 parts by mass or less, more preferably 2 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of aliphatic polycarbonate diol. By blending the amount of 1,6-hexanediol within the above range, the durability of the obtained adhesive layer can be improved, and the solubility in a solvent can be improved.
[0047] The solvent used in the production of the polycarbonate polyurethane diol is not particularly limited as long as it can dissolve the aliphatic polycarbonate diol, 1,6-hexanediol, and isophorone diisocyanate and does not react with the solvent contained in the first agent. For example, from the viewpoint of compatibility with the solvent contained in the first agent and processability during lamination, a carboxylic acid ester solvent such as ethyl acetate can be used.
[0048] The number average molecular weight of the polycarbonate polyurethane polyol is preferably, for example, from 7000 to 13000. When the number average molecular weight is within the above range, the reactivity with the polyisocyanate compound contained in the second agent can be improved, and the solubility in a solvent can be improved.
[0049] The hydroxyl value of the polycarbonate polyurethane polyol is preferably, for example, 10 mgKOH / g or more and 50 mgKOH / g or less. By having the hydroxyl value within the above range, most of the polyisocyanate compound contained in the second agent can be reacted with the polycarbonate polyurethane polyol, and the reaction with the polyisocyanate compound contained in the second agent can be promoted.
[0050] Here, the hydroxyl value is a value measured in accordance with JIS K1557.
[0051] (c) a mixture of polycarbonate polyol and polycarbonate polyurethane polyol In the present disclosure, as described above, the polycarbonate-based polyol preferably contains a mixture of the above-mentioned polycarbonate polyol and the above-mentioned polycarbonate polyurethane polyol. The ratio of the polycarbonate polyol and the polycarbonate polyurethane polyol in the mixture is preferably, for example, 10 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the polycarbonate polyurethane polyol. By having the ratio of the polycarbonate polyol and the polycarbonate polyurethane polyol within the above range, the adhesion can be appropriately reduced and the reaction between the polycarbonate polyurethane polyol and the polyisocyanate compound contained in the second agent can be easily caused.
[0052] (d) Polycarbonate-based polyol In the present disclosure, it is preferable that the polycarbonate-based polyol does not contain a polyester skeleton. Since a polyester skeleton is easily hydrolyzed, by not containing a polyester skeleton in the polycarbonate-based polyol, deterioration of the moist heat resistance caused by the polyester skeleton can be suppressed.
[0053] The fact that the polycarbonate-based polyol does not contain a polyester skeleton can be confirmed, for example, by infrared spectroscopy (FT-IR).
[0054] In the polycarbonate polyol, the content of the polyester skeleton is, for example, preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 0 part by mass, relative to 100 parts by mass of the polycarbonate skeleton. By having the content of the polyester skeleton within the above range, deterioration of moist heat resistance due to the polyester skeleton can be suppressed.
[0055] The content of the polyester skeleton can be determined, for example, based on the peak ratio of an IR spectrum obtained by infrared spectroscopy (FT-IR). Alternatively, analysis may be performed in combination with nuclear magnetic resonance spectroscopy (NMR).
[0056] (2) First ultraviolet absorber The first ultraviolet absorber in the present disclosure is a mixture of 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.
[0057] 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine are compounds represented by the following formulas, respectively.
[0058] [ka]
[0059] The first ultraviolet absorbing agent may be a commercially available product, specifically, Tinuvin 400 manufactured by BASF Japan Ltd.
[0060] The content of the first ultraviolet absorbing agent is 1 part by mass or more and 4 parts by mass or less, preferably 1.5 parts by mass or more and 2.5 parts by mass or less, based on 100 parts by mass of the polycarbonate-based polyol. Since the first ultraviolet absorbing agent can function as a compatibilizer as described above, if the content is too small, the transparency of the obtained adhesive layer may decrease. In addition, if the content is too large, it may decompose itself and turn yellow.
[0061] (3) Second ultraviolet absorber The second ultraviolet absorber in the present disclosure is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine.
[0062] 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine is a compound represented by the following formula.
[0063] [ka]
[0064] The second ultraviolet absorbing agent may be a commercially available product, specifically, Tinuvin 479 manufactured by BASF Japan Ltd.
[0065] The content of the second ultraviolet absorber is 8 parts by mass or more and 10.5 parts by mass or less, preferably 9.5 parts by mass or more and 10.5 parts by mass or less, based on 100 parts by mass of the polycarbonate polyol. If the content is too small, sufficient light resistance may not be obtained. On the other hand, if the content is too large, although light resistance is improved, it is easy to become cloudy, and the transparency of the obtained adhesive layer may decrease.
[0066] (4) Light stabilizers The light stabilizer in the present disclosure is not particularly limited, and for example, a hindered amine light stabilizer (HALS) can be used. Examples of the hindered amine light stabilizer include NOR type hindered amine light stabilizers, NR type hindered amine light stabilizers, and NH type hindered amine light stabilizers. Among them, from the viewpoint of the performance of HALS, NOR type hindered amine light stabilizers and NR type hindered amine light stabilizers are preferred.
[0067] Examples of the NR-type hindered amine light stabilizer include bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, a copolymer of (4-hydroxy-2,2,6,6-tetramethyl-piperidin-1-yl)ethanol and butanedioic acid, N,N',N",N"'-tetrakis(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)triazin-2-yl)-4,7-diazadecane-1,10-diamine, and bis(1,2,2,6,6-pentamethyl-4-pyridinyl)[[3,5-bis(1,1 dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate.
[0068] Commercially available products can be used as the NR-type hindered amine light stabilizer. Specific examples include Tinuvin 292, Tinuvin 111FDL, and Tinuvin 144 manufactured by BASF Japan Ltd. Tinuvin 292 manufactured by BASF Japan Ltd. is a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate. Tinuvin 111FDL manufactured by BASF Japan Ltd. is a mixture of about 50% of a copolymer of (4-hydroxy-2,2,6,6-tetramethyl-piperidin-1-yl)ethanol and butanedioic acid and about 50% of N,N',N",N"'-tetrakis(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)triazin-2-yl)-4,7-diazadecane-1,10-diamine. Tinuvin 144 manufactured by BASF Japan Ltd. is bis(1,2,2,6,6-pentamethyl-4-pyridinyl)[[3,5-bis(1,1 dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate.
[0069] From the viewpoint of dispersibility, the molecular weight of the light stabilizer is preferably, for example, 800 or less.
[0070] The light stabilizers may be used alone or in combination of two or more kinds.
[0071] The content of the light stabilizer is, for example, preferably 0.5 parts by mass or more and 3.0 parts by mass or less, more preferably 0.7 parts by mass or more and 2.5 parts by mass or less, and even more preferably 1.0 parts by mass or more and 2.0 parts by mass or less, relative to 100 parts by mass of the polycarbonate-based polyol. By having the content within the above range, the light resistance of the obtained adhesive layer can be improved. On the other hand, if the content is too high, the transparency and adhesion of the obtained adhesive layer may be reduced due to bleeding out or aggregation of the light stabilizer.
[0072] (5) Additives The first agent in the present disclosure may contain additives such as a tackifier, an antioxidant, a filler, a plasticizer, a softening point improver, and a catalyst, as necessary. Examples of the tackifier include rosin-based resins and terpene-based resins. Examples of the filler include inorganic fillers.
[0073] (6) Solvent In the present disclosure, the first agent preferably contains a solvent from the viewpoint of application and handling. The solvent is not particularly limited, and examples thereof include carboxylic acid esters such as ethyl acetate, methyl acetate, and methyl propionate. The solvent contained in the first agent and the solvent contained in the second agent may be the same or different from each other.
[0074] 2. Second agent The second agent constituting the adhesive composition of the present disclosure contains a polyisocyanate compound.
[0075] (1) Polyisocyanate compounds The polyisocyanate compound is a compound having two or more isocyanate groups in one molecule. The polyisocyanate compound reacts with the hydroxyl groups of the polycarbonate-based polyol to form a urethane bond, and can crosslink the polycarbonate-based polyol.
[0076] The polyisocyanate compound is not particularly limited, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, or adducts, isocyanurates, or biuret forms thereof, or urethane prepolymers having isocyanate groups at their terminals obtained by reacting a polyol with an excess of polyisocyanate.
[0077] Examples of the aliphatic polyisocyanate include hexamethylene diisocyanate (HDI) and lysine diisocyanate (LDI).
[0078] Examples of alicyclic polyisocyanates include isophorone diisocyanate (IPDI), cyclohexane-1,4-diisocyanate, hydrogenated xylylene diisocyanate (H6XDI), dicyclohexylmethane diisocyanate (H 12 MDI), 1,3-bis(isocyanatomethyl)cyclohexane, and norbornane diisocyanate.
[0079] Examples of aromatic polyisocyanates include diphenylmethane diisocyanates (MDI) such as tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate, and 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate; phenylene diisocyanates (PDI) such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, and 1-chloro-2,4-phenylene diisocyanate; diphenyl diisocyanates such as 4,4'-diphenyl diisocyanate, 3,3'-dimethyl-4,4'-diphenyl diisocyanate, and 3,3'-dimethoxy-4,4'-diphenyl diisocyanate; and naphthalene diisocyanates (NDI) such as xylylene diisocyanate (XDI), tetramethylxylene diisocyanate (TMXDI), and 1,5-naphthalene diisocyanate.
[0080] The polyisocyanate compounds may be used alone or in combination of two or more kinds.
[0081] Among them, from the viewpoint of improving reactivity with hydroxyl groups, a mixture of hexamethylene diisocyanate (HDI) and isocyanurate-modified isophorone diisocyanate (nurate-modified IPDI) is preferred. When using a mixture of HDI and nurate-modified IPDI, the mass ratio of HDI to nurate-modified IPDI is preferably within the range of, for example, 70:30 to 50:50.
[0082] (2) Solvent In terms of application and handling, the second agent in the present disclosure preferably contains a solvent. The solvent is not particularly limited, and examples thereof include carboxylic acid esters such as ethyl acetate, methyl acetate, and methyl propionate.
[0083] 3. Combination of the first and second agents The mixing ratio of the first and second agents is preferably, for example, a ratio of isocyanate groups derived from the polyisocyanate compound to hydroxyl groups derived from the polycarbonate polyol (isocyanate groups derived from the polyisocyanate compound / hydroxyl groups derived from the polycarbonate polyol) of 1.0 to 3.5, more preferably 1.2 to 3.0. By keeping the ratio within the above range, an adhesive capable of firmly bonding each member can be obtained.
[0084] 4. Silane coupling agents The adhesive composition of the present disclosure may contain a silane coupling agent, if necessary, in addition to the first and second agents. Examples of the silane coupling agent include silane monomers such as methyltrimethoxysilane and methyltriethoxysilane; vinyl silanes such as vinyltriethoxysilane and vinyltrimethoxysilane; methacryl silanes such as 3-methacryloxypropylethoxysilane and 3-methacryloxypropylmethoxysilane; and epoxy silanes such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0085] The amount of the silane coupling agent added is preferably, for example, 1 part by mass or more and 3 parts by mass or less per 100 parts by mass of the total solid content of the first agent and the second agent. By keeping the amount added within the above range, good adhesion can be obtained and durability can be improved.
[0086] 5.Applications The adhesive composition according to the present disclosure is a two-part adhesive composition in which a first part and a second part are mixed immediately before use.
[0087] The adhesive composition of the present disclosure can be used, for example, in a solar cell module. The adhesive composition can be used, for example, for bonding each member constituting a surface protective sheet of a solar cell module, specifically, for bonding each member constituting a transparent sheet used as a surface protective sheet. In particular, the adhesive composition can be used preferably for bonding a fluorine-based resin layer located on the outermost surface of a transparent sheet to a barrier layer, since the adhesive composition can provide an adhesive layer that is excellent in weather resistance, particularly in moist heat resistance and light resistance, and also in transparency.
[0088] The adhesive composition according to the present disclosure can be used, for example, in a resin sheet made of a multilayer sheet that replaces glass. The adhesive composition can be used, for example, to bond each member constituting the resin sheet made of a multilayer sheet.
[0089] B. Transparent sheets for solar cell modules The transparent sheet for a solar cell module in the present disclosure has two embodiments, each of which will be described below separately.
[0090] 1. First embodiment of transparent sheet for solar cell module The transparent sheet for a solar cell module in this embodiment has a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, and the weather-resistant adhesive layer is a polycarbonate-based polyurethane resin which is a reaction product of a polycarbonate-based polyol and a polyisocyanate compound, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis The composition contains a first ultraviolet absorber which is a mixture of (2,4-dimethylphenyl)-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer, and the content of the first ultraviolet absorber is 1 part by mass or more and 4 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol, and the content of the second ultraviolet absorber is 8 parts by mass or more and 10.5 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol.
[0091] Fig. 1 is a schematic cross-sectional view showing an example of the transparent sheet for a solar cell module in this embodiment. As shown in Fig. 1, the transparent sheet for a solar cell module 1 has a fluorine-based resin layer 2, a weather-resistant adhesive layer 3, and a barrier layer 4 in this order. The weather-resistant adhesive layer 3 is a polycarbonate-based polyurethane resin which is a reaction product of a polycarbonate-based polyol and a polyisocyanate compound, and 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy The composition contains a first ultraviolet absorber which is a mixture of 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)]-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer, and the content of the first ultraviolet absorber and the content of the second ultraviolet absorber are within a specified range.
[0092] The transparent sheet 1 for a solar cell module may also have a substrate layer 6 located on the side of the weather-resistant adhesive layer 3 opposite the fluororesin layer 2. In FIG. 1, the substrate layer 6 is located on the side of the barrier layer 4 opposite the weather-resistant adhesive layer 3, but this is not limited thereto, and although not shown, the substrate layer may be located between the weather-resistant adhesive layer and the barrier layer. The transparent sheet 1 for a solar cell module may also have an adhesive layer 5 between the barrier layer 4 and the substrate layer 6.
[0093] The transparent sheet for solar cell module in this embodiment has a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, thereby being able to impart weather resistance and barrier properties. In addition, in the transparent sheet for solar cell module in this embodiment, the weather-resistant adhesive layer is a polycarbonate-based polyurethane resin which is a reaction product of a polycarbonate-based polyol and a polyisocyanate compound, and 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl) The adhesive composition according to the present invention contains a first ultraviolet absorber which is a mixture of 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer, and the content of the first ultraviolet absorber and the content of the second ultraviolet absorber are within a predetermined range, so that a weather-resistant adhesive layer having excellent weather resistance, particularly excellent moist heat resistance and light resistance, and excellent transparency can be obtained, as described in the above section "A. Adhesive composition". Therefore, the transparent sheet for solar cell module in this embodiment can be used as a substitute for glass.
[0094] Hereinafter, each component of the transparent sheet for a solar cell module in this embodiment will be described.
[0095] (1) Weather-resistant adhesive layer The weather-resistant adhesive layer in this embodiment is a member disposed between the fluororesin layer and the barrier layer, and is a polycarbonate-based polyurethane resin which is a reaction product of a polycarbonate-based polyol and a polyisocyanate compound, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. The composition contains a first ultraviolet absorber which is a mixture of 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer, and the content of the first ultraviolet absorber and the content of the second ultraviolet absorber are within a specified range.
[0096] The polycarbonate-based polyol, the polyisocyanate compound, the first ultraviolet absorber, the second ultraviolet absorber, and the light stabilizer are the same as those described above in the section "A. Adhesive composition."
[0097] That is, the weather-resistant adhesive layer can contain a cured product of the above-mentioned adhesive composition.
[0098] The polycarbonate-based polyurethane resin contained in the weather-resistant adhesive layer preferably does not contain a polyester skeleton. Since a polyester skeleton is easily hydrolyzed, the polycarbonate-based polyol does not contain a polyester skeleton, so that deterioration of the moist heat resistance caused by the polyester skeleton can be suppressed.
[0099] The fact that the polycarbonate-based polyurethane resin does not contain a polyester skeleton can be confirmed, for example, by infrared spectroscopy (FT-IR).
[0100] In the polycarbonate-based polyurethane resin, the content of the polyester skeleton is, for example, preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 0 part by mass, relative to 100 parts by mass of the polycarbonate skeleton. By having the content of the polyester skeleton within the above range, deterioration of moist heat resistance due to the polyester skeleton can be suppressed.
[0101] The content of the polyester skeleton can be determined, for example, based on the peak ratio of an IR spectrum obtained by infrared spectroscopy (FT-IR). Alternatively, analysis may be performed in combination with nuclear magnetic resonance spectroscopy (NMR).
[0102] The thickness of the weather-resistant adhesive layer can be appropriately set according to the desired adhesive strength, for example, 1.0 μm or more and 10 μm or less, preferably 4 μm or more and 10 μm or less. If the thickness of the weather-resistant adhesive layer is within the above range, sufficient adhesive strength can be obtained. In addition, if the thickness of the weather-resistant adhesive layer is too thin, ultraviolet absorption may be insufficient.
[0103] The weather-resistant adhesive layer can be formed, for example, by mixing the first and second parts of the adhesive composition, applying the mixture to the surface of the fluororesin layer, the barrier layer, or the substrate layer, and drying. The mixture is cured in a state in which the fluororesin layer and the barrier layer or the substrate layer are laminated with a film of the mixture interposed therebetween, to form a weather-resistant adhesive layer.
[0104] The method for applying the mixture is not particularly limited, and examples thereof include gravure coating, roll coating, kiss coating, brush coating, etc. The amount of coating may be such that the thickness after drying falls within a predetermined range, for example, 1.0 g / m2 in a dry state. 2 More than 10.0g / m 2 It can be as follows:
[0105] Inside the film of the mixture, the hydroxyl group contained in the polycarbonate polyol reacts with the isocyanate group contained in the polyisocyanate compound to form a urethane bond, and a curing reaction proceeds. Through this reaction, the polycarbonate polyol is crosslinked by the polyisocyanate compound, resulting in a high molecular weight. When the polycarbonate polyol is sufficiently crosslinked, the film of the mixture hardens and becomes a weather-resistant adhesive layer.
[0106] (2) Fluorine-based resin layer The fluororesin layer in this embodiment is a member arranged on the outermost surface of the light-receiving surface side of the transparent sheet for a solar cell module. When the transparent sheet for a solar cell module is used as a surface protective sheet for a solar cell module, the fluororesin layer is a member that can be arranged on the outermost surface of the light-receiving surface side of the solar cell module. The fluororesin layer contains a fluororesin, and therefore can exhibit weather resistance.
[0107] The fluororesin layer has transparency. Specifically, the total light transmittance of the fluororesin layer is preferably 80% or more, and more preferably 85% or more. Here, the total light transmittance can be measured in accordance with JIS K7361. The total light transmittance of other layers of the transparent sheet for solar cell module can be measured in the same manner.
[0108] The fluororesin constituting the fluororesin layer is preferably a transparent one, specifically, tetrafluoroethylene-ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.
[0109] The fluororesin layer may contain various additives for the purpose of improving, for example, processability, heat resistance, water resistance, light resistance, weather resistance, and the like.
[0110] The thickness of the fluororesin layer is preferably, for example, 10 μm or more and 30 μm or less. If the thickness of the fluororesin layer is too thin, the processability may be poor. If the thickness of the fluororesin layer is too thick, the cost may be high.
[0111] As the fluororesin layer, a fluororesin film that has been formed into a film shape in advance can be used.
[0112] (3) Barrier layer The barrier layer in this embodiment is disposed on the surface of the weather-resistant adhesive layer opposite the fluororesin layer, and is a member that imparts water vapor barrier properties to the transparent sheet for a solar cell module.
[0113] The barrier layer has transparency. Specifically, the total light transmittance of the barrier layer is preferably 80% or more, and more preferably 85% or more.
[0114] The barrier layer is not particularly limited as long as it has water vapor barrier properties and transparency, and examples thereof include a barrier film having a resin substrate and a thin film layer.
[0115] In the barrier film, the arrangement of the resin substrate and the thin film layer is not particularly limited, but it is preferable that the barrier layer has the thin film layer and the resin substrate in this order from the fluororesin layer side. When the transparent sheet for solar cell module in this embodiment is used as a surface protective sheet for a solar cell module, the transparent sheet for solar cell module is arranged so that the surface opposite to the fluororesin layer faces the solar cell element. Therefore, when the barrier layer has the thin film layer and the resin substrate in this order from the fluororesin layer side, the resin substrate is located on the inside and the thin film layer is located on the outside in the barrier layer, so that the thin film layer can protect the resin substrate from external moisture.
[0116] The barrier layer is not particularly limited as long as it has water vapor barrier properties and transparency, and has a resin substrate and a thin film layer, but a vapor deposition film is usually used.
[0117] The structure of the barrier layer will be described below.
[0118] (a) Thin film layer The thin film layer is not particularly limited as long as it has transparency and can provide water vapor barrier properties, and examples thereof include metal films and inorganic compound films.
[0119] Examples of metals constituting the metal film include metals such as aluminum, nickel, stainless steel, iron, copper, and titanium, and alloys containing these metals.
[0120] Examples of inorganic compounds constituting the inorganic compound film include oxides, oxynitrides, nitrides, oxycarbides, and oxycarbonitrides of metal elements or nonmetal elements such as silicon, aluminum, magnesium, calcium, potassium, tin, sodium, titanium, boron, lead, yttrium, zirconium, cerium, and zinc. Specific examples include silicon oxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide, silicon-zinc alloy oxide, indium alloy oxide, silicon nitride, aluminum nitride, titanium nitride, silicon oxynitride, and zinc silicon oxide. The inorganic compounds may be used alone or in combination of two or more.
[0121] Among these, the thin film layer is preferably an inorganic compound film, since when the thin film layer is an inorganic compound film, the insulating properties can be improved.
[0122] The thin film layer may be a vapor-deposited film formed by a vapor deposition method, or a coated film formed by a coating method. Among these, a vapor-deposited film is preferred. A vapor-deposited film has high adhesion to a resin substrate and can exhibit high water vapor barrier properties.
[0123] The thin film layer may be a single layer or a multilayer. When the thin film layer is a multilayer, it may have only a vapor deposition film, may have only a coating film, or may have both a vapor deposition film and a coating film. When the thin film layer is a multilayer, it may combine films of the same composition, or may combine films of different compositions.
[0124] The thickness of the thin film layer is, for example, preferably 1 nm or more, more preferably 10 nm or more. By having the thickness of the thin film layer in the above range, sufficient water vapor barrier properties can be obtained. On the other hand, the thickness of the thin film layer is, for example, preferably 300 nm or less, more preferably 200 nm or less. By having the thickness of the thin film layer in the above range, the occurrence of breakage or cracks in the thin film layer can be suppressed.
[0125] Examples of the method for forming the thin film layer include deposition and coating. Among them, deposition is preferred for the above reasons. Examples of the deposition include physical vapor deposition such as vacuum deposition, sputtering, ion plating, and ion cluster beam, and chemical vapor deposition such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.
[0126] In the case of the vapor deposition method, the vapor deposition may be performed once or multiple times. That is, the vapor-deposited film may be a single layer formed by a single vapor deposition, or a multilayer formed by multiple vapor depositions.
[0127] (b) Resin base material The resin substrate is not particularly limited as long as it has transparency and can support the thin film layer, but it is preferable that it has heat resistance. Examples of the resin constituting the resin substrate include polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyimide resins, polycarbonate resins, polystyrene resins, polyamide resins such as various nylons, polyetherimide resins, polyetherketone resins, polyphenylene sulfide resins, polyacrylate resins, polyester ether resins, polyamideimide resins, polymethyl methacrylate resins, fluororesins, polyphenylene ether resins, and polyolefin resins such as polypropylene. The resin may be used alone or in combination of two or more.
[0128] The resin substrate may contain additives, such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0129] The resin substrate may be subjected to a surface treatment, which can improve adhesion to the thin film layer.
[0130] The resin substrate may be unstretched, or may be uniaxially or biaxially stretched.
[0131] Furthermore, the resin substrate may or may not have transparency.
[0132] The thickness of the resin substrate is not particularly limited as long as it can support the thin film layer, and is preferably 6 μm or more, and more preferably 9 μm or more. The thickness of the resin substrate is within the above range, so that dimensional stability and heat resistance can be imparted. On the other hand, the thickness of the resin substrate is preferably 150 μm or less, and more preferably 50 μm or less. The thickness of the resin substrate is within the above range, so that the handleability can be improved.
[0133] (c) Barrier layer In the present embodiment, when the barrier layer has a barrier film having a resin substrate and a thin film layer, it may have one barrier film or may have multiple barrier films. When the barrier layer has multiple barrier films, each barrier film may be laminated via an adhesive layer to form a laminate.
[0134] (4) Base material layer The transparent sheet for a solar cell module in this embodiment may have a substrate layer located on the side of the weather-resistant adhesive layer opposite to the fluororesin layer.
[0135] The substrate layer being located on the side of the weather-resistant adhesive layer opposite the fluororesin layer means that the substrate layer is located at any position on the side of the weather-resistant adhesive layer opposite the fluororesin layer. The substrate layer may be located, for example, between the weather-resistant adhesive layer and the barrier layer, or may be located on the side of the barrier layer opposite the weather-resistant adhesive layer.
[0136] As for the arrangement of the substrate layer, it is particularly preferred that the substrate layer is arranged on the surface of the barrier layer opposite the weather-resistant adhesive layer. As described above, when the transparent sheet for a solar cell module in this embodiment is used as a surface protective sheet for a solar cell module, the transparent sheet for a solar cell module is arranged so that the surface opposite the fluororesin layer faces the solar cell element, and therefore, when the barrier layer and the substrate layer are arranged in this order from the weather-resistant adhesive layer side, the barrier layer is located on the outer side than the substrate layer, so that the intrusion of moisture from the outside can be further suppressed.
[0137] The substrate layer has transparency. Specifically, the total light transmittance of the substrate layer is preferably 80% or more, and more preferably 85% or more.
[0138] The base layer is not particularly limited as long as it has transparency, but it is preferable that it has heat resistance. Examples of the resin constituting the base layer include polyester resins such as polyethylene terephthalate and polyethylene naphthalate. Among them, polyethylene terephthalate is preferable from the viewpoints of transparency, weather resistance, cost, processability, etc.
[0139] The thickness of the base layer is, for example, preferably 50 μm to 280 μm, and more preferably 75 μm to 200 μm. By having the thickness of the base layer within the above range, sufficient insulation properties and strength can be obtained.
[0140] (5) Adhesion layer 2, the transparent sheet for a solar cell module in this embodiment may have an adhesion layer 7 on the outermost surface opposite to the fluororesin layer 2. When the transparent sheet for a solar cell module in this embodiment is used as a surface protective sheet for a solar cell module, the adhesion layer can improve the adhesion between the transparent sheet for a solar cell module and the encapsulant layer.
[0141] The adhesion layer is a so-called primer layer. As the primer composition used for forming the adhesion layer, a primer having transparency can be appropriately selected from various conventionally known primer coating agents. For example, a primer composition containing a polyolefin resin and using an aqueous medium as the main solvent, a primer composition containing a crosslinkable resin and a crosslinking agent and using an organic medium as the main solvent, etc. can be mentioned. Among them, when the substrate layer contains a polyester resin and the encapsulant layer of the solar cell module contains a polyolefin resin such as ethylene-vinyl acetate copolymer (EVA), a primer composition containing an acid-modified polyolefin resin and using an aqueous medium as the main solvent is preferably used. By using an acid-modified polyolefin resin as the base resin, the adhesion between the substrate layer and the encapsulant layer can be further improved. This is described, for example, in JP 2013-74172 A.
[0142] The thickness of the adhesive layer is appropriately set according to the desired transparency and adhesive strength. Specifically, the thickness of the adhesive layer is preferably 0.5 μm or more and 10.0 μm or less, and more preferably 0.8 μm or more and 5 μm or less. By setting the thickness of the adhesive layer within the above range, sufficient adhesiveness and good blocking resistance can be imparted, and the manufacturing cost can also be reduced.
[0143] (6) Adhesive layer The transparent sheet for a solar cell module in this embodiment may have an adhesive layer between the barrier layer and the base layer.
[0144] The adhesive used in the adhesive layer is not particularly limited as long as it has transparency, and examples thereof include pressure-sensitive adhesives, thermoplastic adhesives, curable adhesives, etc. In addition, for example, a urethane adhesive can be used in the adhesive layer, and preferably a urethane adhesive containing a polycarbonate-based polyol and a polyisocyanate compound can be used. The polycarbonate-based polyol and polyisocyanate compound can be the same as the polycarbonate-based polyol and polyisocyanate compound described in the above section "A. Adhesive composition".
[0145] (7) Characteristics of transparent sheets for solar cell modules The transparent sheet for a solar cell module in this embodiment has water vapor barrier properties. Specifically, the water vapor transmission rate of the transparent sheet for a solar cell module is 10 -1 g / (m 2 10 ·day) or less, preferably 10 -2 g / (m 2 ·day) or less, more preferably 10 -3 g / (m 2 ·day) or less.
[0146] The water vapor permeability of the transparent sheet for solar cell modules can be measured in accordance with ISO15106-5:2015 (differential pressure method) using a water vapor permeability measuring device under conditions of a temperature of 40° C. and a relative humidity difference of 90% RH. For example, the water vapor permeability measuring device that can be used is “DELTAPERM” manufactured by Technolox.
[0147] 2. Second embodiment of transparent sheet for solar cell module The transparent sheet for a solar cell module of this embodiment has a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, and the weather-resistant adhesive layer is a polycarbonate-based polyurethane resin, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. a first ultraviolet absorber which is a mixture of 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)]-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer; and the transparent sheet for a solar cell module has a haze of 15% or less, a wavelength of 300 nm or more and 400 nm or less, and an illuminance of 1000 W / m 2 When the transparent sheet for a solar cell module is irradiated with light of this order, the time required for the reduction in total light transmittance of the transparent sheet for a solar cell module to reach 5% is 500 hours or longer.
[0148] The transparent sheet for solar cell module in this embodiment has a fluorine-based resin layer, a weather-resistant adhesive layer, and a barrier layer in this order, thereby being able to impart weather resistance and barrier properties. Also, in the transparent sheet for solar cell module in this embodiment, the weather-resistant adhesive layer is a first layer which is a mixture of a polycarbonate-based polyurethane resin, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. It contains an ultraviolet absorber, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer, and the haze is within a predetermined range, and the time until the decrease rate of the total light transmittance reaches a predetermined value when a predetermined light resistance test is performed is within a predetermined range, so that a weather-resistant adhesive layer having excellent weather resistance, particularly excellent moist heat resistance and light resistance, and excellent transparency, can be obtained, as in the first embodiment. Therefore, the transparent sheet for solar cell module in this embodiment can be used as a substitute for glass.
[0149] In this embodiment, the haze of the transparent sheet for solar cell module is 20% or less, preferably 10% or less. By having the haze in the above range, a transparent sheet for solar cell module having excellent transparency can be obtained, that is, the weather-resistant adhesive layer can have excellent transparency.
[0150] Here, the haze can be measured in accordance with JIS K7136, for example, using a haze meter HM150 manufactured by Murakami Color Research Laboratory Co., Ltd.
[0151] In this embodiment, the wavelength is 300 nm or more and 400 nm or less, and the illuminance is 1000 W / m 2The time required for the transparent sheet for a solar cell module to reduce in total light transmittance by 5% when irradiated with light of this order is 500 hours or more, and preferably 800 hours or more. When the time is within the above range, a transparent sheet for a solar cell module having excellent light resistance can be obtained, that is, the weather-resistant adhesive layer can have excellent light resistance.
[0152] The light resistance of the transparent sheet for a solar cell module can be evaluated by the following test method. First, the transparent sheet for a solar cell module is subjected to a super UV test with a wavelength of 300 nm to 400 nm and an illuminance of 1000 W / m 2 The light resistance test is carried out under the conditions of: Next, the total light transmittance of the transparent sheet for a solar cell module is measured before and after the light resistance test. Next, the decrease rate of the total light transmittance before and after the light resistance test is calculated by the following formula. Reduction rate of total light transmittance (%) = (Total light transmittance before light resistance test - Total light transmittance after light resistance test) / Total light transmittance before light resistance test x 100 Then, the light resistance test is carried out until the reduction rate of the total light transmittance reaches 5%, and the time required for this is measured. The Super UV tester may be, for example, Eye Super UV Tester SUV-W151 manufactured by Iwasaki Electric Co., Ltd. The total light transmittance may be measured in accordance with JIS K7361-1, for example, using a haze meter HM150 manufactured by Murakami Color Research Laboratory Co., Ltd.
[0153] In this embodiment, the retention rate of the peel adhesion strength between the fluororesin layer and the barrier layer after the transparent sheet for solar cell module is left for 48 hours at a temperature of 120° C., a humidity of 85% RH, and a pressure of 1.6 atm is, for example, preferably 50% or more, and more preferably 80% or more. When the retention rate of the peel adhesion strength is within the above range, a transparent sheet for solar cell module having excellent moisture and heat resistance can be obtained, that is, the weather-resistant adhesive layer can have excellent moisture and heat resistance.
[0154] Here, the moist heat resistance of the transparent sheet for solar cell module can be evaluated by the following test method. First, the moist heat resistance test is performed on the transparent sheet for solar cell module using a pressure cooker tester under conditions of 120°C, 85% RH, 1.6 atm, and 48 hours. Next, a 180-degree peel test is performed on the transparent sheet for solar cell module before and after the moist heat resistance test, and the peel adhesion strength between the fluororesin layer and the barrier layer is measured. At this time, the peel test is performed three times, and the average value is taken as the peel adhesion strength. Then, the maintenance rate of the peel adhesion strength after the moist heat resistance test is calculated by the following formula. Peel adhesion strength retention rate (%) = (Peel strength after heat and moisture resistance test / peel strength before heat and moisture resistance test) x 100 As the pressure cooker tester, for example, EHS-221M manufactured by Espec Corporation can be used. Moreover, the peel adhesion strength can be measured by carrying out a 180-degree peel test in accordance with JIS K6854-2. In the 180-degree peel test, the test piece is 15 mm wide, and the measurement conditions are a peel speed of 200 mm / min and a temperature of 23° C. As the peel tester, for example, TENSILON RTA-1150-H manufactured by A&D Co., Ltd. can be used.
[0155] The respective configurations of the transparent sheet for a solar cell module in this embodiment can be the same as those in the first embodiment.
[0156] C. Thin-film solar cell module The thin-film solar cell module in the present disclosure has, in this order, a transparent substrate, a thin-film solar cell element, an encapsulant layer, and a back protective sheet, the transparent substrate being the above-mentioned transparent sheet for a solar cell module, and the transparent sheet for a solar cell module being arranged so that the surface on the base layer side faces the thin-film solar cell element.
[0157] 3 is a schematic cross-sectional view showing an example of a thin-film solar cell module according to the present disclosure. A thin-film solar cell module 10 has, in this order, a transparent substrate 11, a thin-film solar cell element 12, an encapsulant layer 13, and a back surface protective sheet 14. The transparent substrate 11 is the above-mentioned transparent sheet 1 for a solar cell module, and although not shown, the transparent sheet 1 for a solar cell module is disposed so that the surface on the base layer side faces the thin-film solar cell element 12.
[0158] In the thin-film solar cell module of the present disclosure, since the transparent substrate is the above-mentioned transparent sheet for a solar cell module, the solar cell module can be made flexible.
[0159] The configuration of the thin-film solar cell module according to the present disclosure will be described below.
[0160] 1. Transparent substrate The transparent substrate in the present disclosure is the above-mentioned transparent sheet for a solar cell module. The transparent sheet for a solar cell module is disposed so that the surface on the base layer side faces the thin-film solar cell element. The transparent sheet for a solar cell module is the same as that described in the above section "B. Transparent sheet for a solar cell module", and therefore a description thereof will be omitted here.
[0161] 2. Thin-film solar cell elements The thin-film solar cell element in the present disclosure is not particularly limited, and examples thereof include a thin-film silicon solar cell element, a CIS solar cell element, a CIGS solar cell element, a CdTe solar cell element, and a perovskite solar cell element.
[0162] The configuration of each type of thin-film solar cell element may be the same as that of a known thin-film solar cell element.
[0163] 3.Encapsulant layer The encapsulant layer in the present disclosure is a member that encapsulates the thin-film solar cell element. The encapsulant layer is disposed between the thin-film solar cell element and the back protective sheet. The encapsulant layer can be the same as the encapsulant layer used in a general solar cell module, and therefore a description thereof will be omitted here. A preformed encapsulant sheet can be used as the encapsulant layer.
[0164] 4. Back protection sheet The back surface protective sheet in the present disclosure is a member that protects a thin-film solar cell element. The back surface protective sheet may be the same as a back surface protective sheet used in a general solar cell module, and therefore a description thereof will be omitted here.
[0165] 5. Manufacturing method of thin-film solar cell module The manufacturing method of the thin-film solar cell module in the present disclosure is not particularly limited as long as it is a method capable of manufacturing a thin-film solar cell module having a transparent sheet for solar cell module, a thin-film solar cell element, an encapsulant layer, and a back surface protective sheet in this order. For example, a method of thermocompression bonding a laminate having a thin-film solar cell element formed on the surface of the transparent sheet for solar cell module on the substrate layer side, an encapsulant layer, and a back surface protective sheet in this order to be integrated. For example, a vacuum thermal lamination method can be used as the thermocompression bonding method.
[0166] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0167] The present disclosure will be further described below with reference to examples and comparative examples.
[0168] [Example 1] (1) Preparation of First Adhesive Composition (1-1) Preparation of the first agent of the first adhesive composition (a) Production of polycarbonate polyurethane diol In a nitrogen atmosphere, 100 parts by mass of an aliphatic polycarbonate diol having a number average molecular weight of 1000 ("Duranol T5651" manufactured by Asahi Kasei Chemicals Corporation), 5 parts by mass of 1,6-hexanediol, 27.5 parts by mass of isophorone diisocyanate, and 132.5 parts by mass of ethyl acetate were added to a flask equipped with a stirrer. -1 The mixture was heated under reflux until the absorption of isocyanate disappeared, and a 50% solution of polycarbonate polyurethane diol in ethyl acetate was obtained. The hydroxyl value of the obtained resin was 14 mgKOH / g, and the number average molecular weight was about 8000.
[0169] (b) Preparation of the first agent The main component was prepared by mixing 100 parts by mass of the polycarbonate polyurethane diol and 15 parts by mass of an aliphatic polycarbonate diol (Asahi Kasei Chemicals' "Duranol T5651", number average molecular weight 1000). Next, 100 parts by mass of the main component, 2 parts by mass of a first ultraviolet absorber (BASF Japan's "Tinuvin 400"), 10 parts by mass of a second ultraviolet absorber (BASF Japan's "Tinuvin 479"), and 1 part by mass of a light stabilizer (BASF Japan's "Tinuvin 292") were dispersed in a bead mill to prepare a first agent. When using the first agent, ethyl acetate (Showa Denko) was used to adjust the solid content to 45%.
[0170] (1-2) Preparation of the second part of the first adhesive composition 100 parts by mass of the nurate form of isophorone diisocyanate, 150 parts by mass of a bifunctional hexamethylene diisocyanate-based polyisocyanate ("Duranate D101" manufactured by Asahi Kasei Chemicals Corporation), and 250 parts by mass of ethyl acetate were mixed to obtain a 50% ethyl acetate solution of a polyisocyanate compound.
[0171] (1-3) Combination of the first and second agents A first adhesive composition was obtained by blending 100 parts by mass of a 45% ethyl acetate solution as the first agent and 23 parts by mass of a 50% ethyl acetate solution as the second agent.
[0172] (2) Preparation of second adhesive composition (2-1) Preparation of the first part of the second adhesive composition 100 parts by mass of the polycarbonate polyurethane diol and 15 parts by mass of an aliphatic polycarbonate diol (Asahi Kasei Chemicals Corporation's "Duranol T5651", number average molecular weight 1000) were mixed to prepare a main component, which was used as the first agent. When using the first agent, the solid content was adjusted to 45% using ethyl acetate (Showa Denko KK).
[0173] (2-2) Preparation of the second part of the second adhesive composition A 50% ethyl acetate solution of a polyisocyanate compound was obtained in the same manner as the second part of the first adhesive composition.
[0174] (2-3) Combination of the first and second agents A second adhesive composition was obtained by blending 100 parts by mass of a 45% ethyl acetate solution as the first agent and 23 parts by mass of a 50% ethyl acetate solution as the second agent.
[0175] (3) Preparation of transparent sheets for solar cell modules An ETFE film (AGC "Aflex 25N D", thickness 25 μm) was used as the fluororesin layer, a vapor deposition film (Oike Kogyo "25GT3", thickness 38 μm) was used as the barrier layer, and a PET film (DuPont "AP", thickness 150 μm) was used as the substrate layer. The fluororesin layer and the barrier layer were dry laminated using the first adhesive composition, and the barrier layer and the substrate layer were dry laminated using the second adhesive composition. Then, aging was performed at 55°C for 5 days. As a result, a transparent sheet for a solar cell module having a fluororesin layer, a weather-resistant adhesive layer, a barrier layer, an adhesive layer, and a substrate layer in this order was obtained. The thicknesses of the weather-resistant adhesive layer and the adhesive layer were 5 μm.
[0176] [Examples 2 to 6] A transparent sheet for a solar cell module was produced in the same manner as in Example 1, except that in preparing the first agent of the first adhesive composition, the content of each component was changed as shown in Table 1 below.
[0177] [Comparative Example 1] A transparent sheet for a solar cell module was produced in the same manner as in Example 1, except that in preparing the first agent of the first adhesive composition, a polyester diol produced as described below was used as the main component.
[0178] (Production of polyester diol) Under a nitrogen atmosphere, ethylene glycol (32.3 parts by mass), 2,2-dimethyl-1,3-propanediol (270.8 parts by mass), 1,6-hexanediol (122.9 parts by mass), adipic acid (228.1 parts by mass), and isophthalic acid (664 parts by mass) were added to a flask equipped with a stirrer and a nitrogen inlet tube, and the mixture was bubbled with nitrogen at 180°C to 220°C to react until the acid value reached 2 mg KOH / g. Ethyl acetate (860 parts by mass) was then added to obtain a 50% solution of polyester diol in ethyl acetate.
[0179] [Comparative Examples 2 to 6] A transparent sheet for a solar cell module was produced in the same manner as in Example 1, except that in preparing the first agent of the first adhesive composition, the content of each component was changed as shown in Table 1 below.
[0180] [evaluation] (1) Transparency (haze) The haze of the transparent sheet for a solar cell module was measured in accordance with JIS K7136 using a haze meter HM150 manufactured by Murakami Color Research Laboratory Co., Ltd. The transparency was evaluated according to the following criteria. A: Haze is 10% or less. B: Haze is more than 10% and 15% or less. C: Haze is more than 15%.
[0181] (2) Moisture and heat resistance The transparent sheet for a solar cell module was subjected to a moist heat resistance test using a pressure cooker tester (EHS-221M manufactured by Espec Corp.) under conditions of 120° C., 85% RH, 1.6 atm, and 48 hours.
[0182] Next, a 180-degree peel test was performed on the transparent sheet for solar cell modules before and after the moist heat resistance test in accordance with JIS K6854-2 to measure the peel adhesion strength between the fluororesin layer and the barrier layer. The test pieces were 15 mm wide. The measurement was performed using a peel tester (TENSILON RTA-1150-H, manufactured by A&D Co., Ltd.) at a peel speed of 200 mm / min and a temperature of 23°C. The peel test was performed three times, and the average value was taken as the peel adhesion strength. The maintenance rate of the peel adhesion strength after the moist heat resistance test was calculated using the following formula. Peel adhesion strength retention rate (%) = (Peel strength after heat and moisture resistance test / peel strength before heat and moisture resistance test) x 100 The wet heat resistance was evaluated according to the following criteria. A: The peel adhesion strength retention rate is 80% or more. B: The retention rate of peel adhesion strength is 50% or more and less than 80%. C: The retention rate of peel adhesion strength is less than 50%.
[0183] In addition, in the case of a film with a moist heat resistance of A, peeling occurred at the interface between the fluororesin layer and the weather-resistant adhesive layer, while in the case of a film with a moist heat resistance of C, the weather-resistant adhesive layer underwent cohesive failure.
[0184] (3) Light resistance The transparent sheet for solar cell modules was tested using a Super UV tester (Iwasaki Electric Co., Ltd. Eye Super UV Tester SUV-W151) with a wavelength of 300 nm to 400 nm and an illuminance of 1000 W / m 2 The light resistance test was carried out under the following conditions. Next, the total light transmittance of the transparent sheet for a solar cell module before and after the light resistance test was measured using a haze meter HM150 manufactured by Murakami Color Research Laboratory Co., Ltd. in accordance with JIS K7361-1. The decrease rate of the total light transmittance before and after the light resistance test was calculated using the following formula. Reduction rate of total light transmittance (%) = (Total light transmittance before light resistance test - Total light transmittance after light resistance test) / Total light transmittance before light resistance test x 100 The light resistance was evaluated according to the following criteria. A: The light resistance test time required for the total light transmittance to decrease by 5% is 800 hours or more. B: The light resistance test time at which the decrease in total light transmittance reaches 5% is 500 hours or more and less than 800 hours. C: The time required for the light resistance test to result in a decrease in total light transmittance of 5% is less than 500 hours.
[0185] [Table 1]
[0186] From Table 1, it was confirmed that when the first agent of the first adhesive composition used in the weather-resistant adhesive layer has a specified composition, the transparency, moist heat resistance, and light resistance are good. [Explanation of symbols]
[0187] 1. Transparent sheet for solar cell modules 2 … Fluorine resin layer 3 … Weather-resistant adhesive layer 4 … Barrier layer 5 … Adhesive layer 6 … Base material layer 7 … Adhesion layer 10. Thin-film solar cell modules 11 ... Transparent substrate 12 ... Thin-film solar cell elements 13 … Encapsulant layer 14 ... Back protection sheet
Claims
[Claim 1] An adhesive composition for use in a solar cell module, the adhesive composition having a first agent and a second agent, the first agent contains a polycarbonate-based polyol, a first ultraviolet absorber which is a mixture of 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, a second ultraviolet absorber which is 2-[4-(octyl-2-methylethanoate)oxy-2-hydroxyphenyl]-4,6-[bis(2,4-dimethylphenyl)]-1,3,5-triazine, and a light stabilizer; The second agent contains a polyisocyanate compound, The content of the first ultraviolet absorber is 1 part by mass or more and 4 parts by mass or less with respect to 100 parts by mass of the polycarbonate-based polyol, The adhesive composition, wherein the content of the second ultraviolet absorber is 8 parts by mass or more and 10.5 parts by mass or less per 100 parts by mass of the polycarbonate-based polyol.
Citation Information
Patent Citations
Weather-proof agent composition
JP2006307142A
Decorative sheet
JP2008238444A
Solar cell module back surface protective sheet, solar cell module back surface integration sheet, and solar cell module
JP2012074419A
Transparent protective sheet for solar battery module
JP2020072159A
Adhesive composition, transparent sheet for solar cell module, and thin-film solar cell module
JP7615697B2